Preparation, Characterisation and Reactivity of Low Oxidation State d-Block Metal Complexes Stabilised by Extremely Bulky Amide Ligands - Hicks, Jamie (Springer Singapore : Imprint: Springer, 2017)
This thesis describes the synthesis and characterization of numerous metal-metal bonded complexes that are stabilized by extremely bulky amide ligands. It provides a comprehensive overview of the field, including discussions on groundbreaking complexes and reactions, before presenting in detail, exciting new findings from the PhD studies. The thesis appeals to researchers, professors and chemistry undergraduates with an interest in inorganic and/or organometallic chemistry.
Keywords: Chemistry.; Inorganic chemistry.; Organometallic chemistry.; Catalysis.; elektronické knihy; electronic books